Pemanfaatan Media Sosial Tiktok oleh Adira Finance dalam Menyampaikan Content Marketing - Winata, Maria Evelyn; Rusdi, Farid (Prologia, 2024)
Over time, a great deal of technology has been purposefully built to make human activities easier. The internet, inextricably linked to social media, is one of the technical innovations most frequently utilised for communication. Due to the onset of the Covid-19 pandemic, not only have individuals been affected, but the situation has also compelled the entire economy, including financial institutions, to revamp their communication strategies in order to sustain marketing efforts for their products. Adira Finance is a finance company under the supervision of OJK (Financial Services Authority) that provides various product services. The presence of TikTok social media creates ease of effective communication between consumers and companies. Adira Finance utilizes TikTok social media as a medium to deliver marketing content. This research uses the theory of the four pillars of social media support strategies according to Lon Safko and K. Brake (2009), namely communication, collaboration, education, and entertainment. TikTok features a variety of interesting content that is packaged differently, namely short videos. Content formulation of the message to be conveyed is important in using this digital platform. This study collects data through observation and interviews using a qualitative methodology. This research was conducted to find out how the utilization of social media, especially TikTok, by a finance company, namely Adira Finance. The results of this research show that Adira Finance's TikTok content focuses on current trends in social media and the content is packaged in a relaxed and humorous manner. Seiring berjalannya waktu, begitu banyak teknologi yang sengaja diciptakan dan dikembangkan untuk mempermudah aktivitas manusia. Salah satu kemajuan teknologi yang paling sering dimanfaatkan sebagai alat komunikasi yaitu Internet yang tidak lepas dari media sosial. Pandemi COVID-19 membuat seluruh sektor ekonomi, termasuk perusahaan pembiayaan, perlu mengubah strategi komunikasi mereka untuk tetap memasarkan produk mereka. Adira Finance merupakan perusahaan pembiayaan di bawah pengawasan OJK (Otoritas Jasa Keuangan) yang memberikan berbagai pelayanan produk. Kehadiran media sosial TikTok menciptakan kemudahan komunikasi yang efektif antara konsumen dengan perusahaan. Adira Finance memanfaatkan media sosial TikTok sebagai media untuk menyampaikan konten marketing. Penelitian ini menggunakan teori empat pilar strategi pendukung media sosial menurut Lon Safko dan K. Brake yaitu komunikasi, kolaborasi, edukasi, dan hiburan. TikTok menampilkan berbagai konten menarik yang dikemas berbeda yaitu video berdurasi singkat. Formulasi konten terhadap pesan yang ingin disampaikan menjadi hal penting dalam penggunaan platform digital ini. Penelitian ini adalah penelitian kualitatif yang mengumpulkan data melalui wawancara dan observasi. Studi ini bertujuan untuk mengetahui bagaimana Adira Finance, sebuah perusahaan pembiayaan menggunakan media sosial TikTok. Hasil penelitian menunjukkan bahwa konten TikTok Adira Finance berfokus pada tren yang sedang berjalan di media sosial tersebut serta konten dikemas dengan santai dan lucu.